Sosialisasi dan Demonstrasi Pengolahan Sampah Rumah Tangga menjadi Produk Eco-enzyme - Yulia Hasni Pratiwi; Sri Winarni Sofya; Lalu Busyairi Muhsin; Muhammad Eka Putra Ramandha; Nyoman Bagus Aji K (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
Garbage is a crucial problem faced by all countries in the world, including Indonesia. The waste generation in the province of NTB in 2021 reached 2,637 tons/day, which comes from 10 districts/cities in NTB. Of this amount, only a small portion, namely around 20%, goes to the Final Disposal Site (TPA) and is recycled, while 80% of the total waste is not managed properly. Therefore, to overcome this problem, we offer an innovative solution to process the waste into "eco-enzyme" products which benefits can be felt by the people of Nyur Lembang Village by made demonstration and Socialization on 4Th June 2023 at the Village meeting hall of Nyur Lembang. The Team makes sure to the Villagers that eco-enzymes are not only a solution to reduce waste around us as a form of caring for the earth, but eco-enzymes are also an environmentally friendly, multifunctional, and very economical solution for Nyur Lembang villagers.